The Relationship of Serum Ferritin and Uterine Contractions - Masoumeh Goudarzi; Ahmad Reza Yazdan-Nik; Sharareh Davazdah-Emami (Iran University of Medical Sciences, 2009)
Background and Aim: Prenatal care is performed in order to diagnose high risk cases. Researches have shown the significant relationship between high serum ferritin levels and preterm delivery. Uterine activity is one of the major risk factors of preterm labor. This study aims to examine relationship between serum ferritin level and uterine contractions.   Material and Method: A descriptive and analytical research design was used to conduct the study. The sample consisted of 322 pregnant women who reffered to health centers in Isfahan. Data were collected by questionnaire (through interview), and also, hospital documents and the results of serum ferritin levels were used for analysis.   Results: Serum ferritin levels according to 10, 25,50,75,90 percentiles were 8.6, 12.3, 20.3, 30.7 and 42.5 ng/ml, respectively. A statistically significant relationship was found between serum ferritin levels (in 28-30 weeks of pregnancy) and uterine contractions (P<0.001).   Conclusion: Our findings suggest that further researches about ferritin level and related factors and pregnancy outcomes are needed. More research in the field of ferritin level and related factors and pregnancy outcomes is suggested.